All Days 2012
DOI: 10.2118/154275-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microemulsion Viscosity on Oil Recovery

Abstract: The physical structure of microemulsions and the degree to which ultra-low IFT is achieved is dependent on a number of parameters including the types and concentrations of surfactants, co-solvents and alkali, crude oil composition, brine composition, temperature and to a lesser extent, pressure. Modifying any one of these variables creates a microemulsion with different properties. The rheological properties of the microemulsion must be adjusted appropriately to achieve good performance under practical reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Figure 4 shows crude #2 emulsions are as viscous as the crude at 68°C when the oil content is 30%, while adding just 1% co-solvent reduces their viscosity over ten-fold. This pattern is seen whenever a tailored co-solvent is added to viscous macroemulsions (Walker et al, 2012).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Figure 4 shows crude #2 emulsions are as viscous as the crude at 68°C when the oil content is 30%, while adding just 1% co-solvent reduces their viscosity over ten-fold. This pattern is seen whenever a tailored co-solvent is added to viscous macroemulsions (Walker et al, 2012).…”
Section: Resultsmentioning
confidence: 93%
“…Macroemulsions can be extremely viscous, and can hurt coreflood performance in terms of oil recovery and excessive pressure drop (Walker et al, 2012). Addition of certain light co-solvents has the effect of destabilizing macroemulsions and encourages the formation of thermodynamically-stable microemulsions with low viscosity (Bourrel and Schechter, 1988;Sahni et al, 2010;Walker et al, 2012). The use of viscous macroemulsions for mobility control has generally not been successful (Mayer et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, a microemulsion is a thermodynamically stable and clear dispersion of oil and water, in combination with surfactant molecules (Ruckenstein 1981;Walker et al 2012). Winsor (1985) identified that for a microemulsion system with a fixed surfactant concentration, selected crude oil, and different salinity, the phase behavior of microemulsion can be classified into three different classes: microemulsion Type I (or lower phase microemulsion), microemulsion Type II (or upper phase microemulsion), and microemulsion Type III (or middle phase microemulsion).…”
Section: Methodsmentioning
confidence: 99%
“…Microemulsions are thermodynamically stable and clear dispersion of water and oil when combined with surfactant solution (Walker et al, 2012) Windsor (1985) discussed the classification of microemulsion phases. Microemulsion was classified into three different types; type I also known as the lower phase microemulsion, type II (upper phase microemulsion) and type III (middle phase microemulsion).…”
Section: Procedures For Experimentsmentioning
confidence: 99%